The Relationship Between Self-Directed Learning and Mathematical Literacy Skills Among Grade XI Students: A Correlational Study - Zahrani Putri Setiabudi; Fitri Alyani (MASI Mandiri Edukasi, 2025)
This scholarly investigation examines the relationship between self-directed learning and proficiency in mathematical literacy among students. The methodology employed in this study is quantitative, utilizing a correlational approach. The sampling technique adopted was convenience sampling, encompassing 143 high school students from Jakarta. The instruments employed for data collection comprised a self-directed learning questionnaire alongside a mathematical literacy assessment. The questionnaire was meticulously crafted to evaluate the degree to which students exhibit initiative, responsibility, and self-directed learning capabilities. Conversely, the mathematical literacy assessment was designed to gauge students' proficiency in comprehending, interpreting, and resolving contextualized mathematical challenges. The data analysis incorporated a correlation test to determine the relationship between the two variables. The results revealed a statistically significant correlation between self-directed learning and students' mathematical literacy competencies, with a significance value of 0.035 below the threshold of α = 0.05, alongside a Pearson correlation coefficient of r = 0.176. Consequently, it can be inferred that an increase often follows an increase in the level of students self-directed learning in mathematical literacy. However, because the correlation value is very low, the effect of self-directed learning on mathematical literacy is considered small, suggesting that other factors may also play a role in influencing students' mathematical literacy skills.